2007
DOI: 10.3758/bf03193310
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in immediate serial recall: Dissociating chunk formation and capacity

Abstract: We assessed the contribution of two hypothesized mechanisms to impaired memory performance of older adults in an immediate serial recall task: decreased temporary information storage in a capacity-limited mechanism, such as the focus of attention, and a deficit in binding together different components into cohesive chunks. Using a method in which paired associations between words were taught at varying levels to allow an identification of multiword chunks (Cowan, Chen, & Rouder, 2004), we found that older adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 76 publications
2
44
1
1
Order By: Relevance
“…Our findings are also relevant to the literature on age-related declines in associative memory (e.g., Chalfonte & Johnson, 1996;Naveh-Benjamin, 2000;Naveh-Benjamin, Cowan, Kilb, & Chen, 2007). By this view, older adult should show evidence of (i) poorer chunk retrieval due to weaker binding between items within a chunk and (ii) smaller chunks due to reduced processing resources available for associative binding (Naveh-Benjamin et al, 2007).…”
Section: Chunk Size and Retrievalmentioning
confidence: 67%
“…Our findings are also relevant to the literature on age-related declines in associative memory (e.g., Chalfonte & Johnson, 1996;Naveh-Benjamin, 2000;Naveh-Benjamin, Cowan, Kilb, & Chen, 2007). By this view, older adult should show evidence of (i) poorer chunk retrieval due to weaker binding between items within a chunk and (ii) smaller chunks due to reduced processing resources available for associative binding (Naveh-Benjamin et al, 2007).…”
Section: Chunk Size and Retrievalmentioning
confidence: 67%
“…Furthermore, previous studies also demonstrated a reduced WM span in older adults (e.g., Norman, Kemper, & Kynette, 1992). For example, Park et al (2002) reported that WM performance linearly declined as a function of participants' age, showing that older adults have a smaller WM capacity than young adults (see also Foos, 1989;Naveh-Benjamin, Cowan, Kilb, & Chen, 2007).…”
Section: Attentional Resources and Older Adults' Associative Deficit mentioning
confidence: 92%
“…For the most part, high levels of proportional feature binding accuracy were observed in baseline conditions across the three experiments. This reveals that when 23 Running head: Working memory in spoken instructions the participant accessed each action ÔchunkÕ (see also Gilchrist, Cowan, & NavehBenjamin, 2009;Naveh-Benjamin, Cowan, Kilb, & Chen, 2007) by recalling the correct movement, they were highly likely to then complete this chunk by producing the appropriate object (in terms of both color and form), potentially indicating that partial loss of binding information in this paradigm was relatively rare. Movementobject chunks may therefore be encoded, retained (possibly within the episodic buffer), and accessed at retrieval in an all-or-none manner, at least when working memory resources are not directed elsewhere.…”
Section: Discussionmentioning
confidence: 99%